Nodal signaling activates the Smad2/3 pathway to regulate stem cell-like properties in breast cancer cells - Gong, Wenchen (Am J Cancer Res, 2017)
Nodal signaling plays several vital roles in the embryogenesis process. However, its reexpression in breast cancer is correlated with cancer progression, metastasis and poor prognosis. Recently, Nodal has also been reported to regulate self-renewal capacity in pancreatic cancer. This study aimed to explore the role of Nodal in breast cancer stem cells (BCSCs) and the underlying mechanisms. Therefore, the immunohistochemistry staining of Nodal in 135 human breast cancer cases was performed to analyzed the relationship of Nodal signaling, clinical outcomes and BCSC marker. And the results showed that high Nodal expression was positively correlated with poor prognosis and BCSC marker expression in breast cancer samples. We further assessed the effects of Nodal in regulating the BCSC properties in breast cancer cell lines and xenografts. Then, SB431542 was administered in vitro and in vivo to explore the function of the Smad2/3 pathway. And we demonstrated that Nodal signaling up-regulated the expression of ALDH1, CD44, CD133, Sox2, Oct4 and Nanog by activating the Smad2/3 pathway, thereby enhancing the tumorigenicity and sphere-forming ability of breast cancer cells. Furthermore, treatment with SB431542 could inhibit the properties of BCSCs in vitro and in vivo. In conclusion, these findings indicate that Nodal signaling may play a vital role in maintaining the BCSC phenotype in breast cancer and serve as a potential target to explore BCSC-specific therapies.